2003
DOI: 10.1113/jphysiol.2003.040147
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic changes in carotid artery diameter in humans during and after strenuous exercise

Abstract: Arterial baroreflex function is altered by dynamic exercise, but it is not clear to what extent baroreflex changes are due to altered transduction of pressure into deformation of the barosensory vessel wall. In this study we measured changes in mean common carotid artery diameter and the pulsatile pressure : diameter ratio (PDR) during and after dynamic exercise. Ten young, healthy subjects performed a graded exercise protocol to exhaustion on a bicycle ergometer. Carotid dimensions were measured with an ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
38
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 33 publications
(41 reference statements)
14
38
4
Order By: Relevance
“…Comparable to a previous report, 33 mechanical BRS was reduced after exercise. This study used the ␣ index for BRS assessment, however, and thus could not differentiate between mechanical G up and G down , both of which were found to decrease similarly in the present study.…”
Section: Mechanical and Neural Alterations After Exercisesupporting
confidence: 76%
“…Comparable to a previous report, 33 mechanical BRS was reduced after exercise. This study used the ␣ index for BRS assessment, however, and thus could not differentiate between mechanical G up and G down , both of which were found to decrease similarly in the present study.…”
Section: Mechanical and Neural Alterations After Exercisesupporting
confidence: 76%
“…Thus sympathetically mediated vasoconstriction may have contributed. Alternatively, Studinger et al (2003) showed that at high work intensities the elevated arterial pressure induces a strong myogenic response in the carotid smooth muscle (Olesen et al 1995). When exercise is terminated and the intraluminal distending pressure suddenly drops, the myogenic smooth muscle contraction is left unopposed, causing a transient vasoconstriction.…”
Section: Carotid Artery Stiffness Indicesmentioning
confidence: 99%
“…Myogenic vasoconstriction results in baroreceptor unloading and consequent sympathetic excitation (Studinger et al 2003). Compliance and distensibility in children and adults decreased following exercise as both coefficients are largely influenced by local pressure (denominator).…”
Section: Carotid Artery Stiffness Indicesmentioning
confidence: 99%
“…5,7,8,10,13). In more realistic analyses, the viscoelastic behavior of arterial walls has been studied by many researchers (4,10,12,20,21,23,24,27,29). To reduce the mathematical complexity, the theory of quasi-linear viscoelasticity (10) has been applied to arteries and other living tissues (e.g., Refs.…”
mentioning
confidence: 99%